A randomized controlled trial of MoodSwings 2.0: An internet‐based self‐management program for bipolar disorder. (21st June 2018) - Gliddon, Emma; Cosgrove, Victoria; Berk, Lesley; Lauder, Sue; Mohebbi, Mohammadreza; Grimm, David; Dodd, Seetal; Coulson, Carolyn; Raju, Karishma; Suppes, Trisha; Berk, Michael
Abstract : Objectives: MoodSwings 2.0 is an online self‐guided intervention for bipolar disorder that includes educational modules, interactive tools, and discussion forums. The primary aim of the study was to determine if participation in MoodSwings 2.0 would result in decreased symptoms of depression and mania compared to the control condition. Secondary aims were to identify improvements in core depression symptoms, quality of life, medication adherence, functioning, and time to relapse. Methods: This was a three‐arm randomized controlled trial that compared two intervention arms against a peer support control group (forum). A total of 304 adults aged 21 to 65 years with a diagnosis of bipolar disorder were assigned to a forum‐only control group (Group 1; n = 102), a forum plus modules treatment group (Group 2; n = 102), or a forum, modules, and tools treatment group (Group 3; n = 100), in addition to usual care. Results: There was a significant intervention impact showing improvement on the primary outcome of depression for Group 2 compared to Group 1 ( P = .05) with effect sizes (Cohen's d ) ranging from 0.17 to 0.43. There was also a significant intervention impact showing improvement on the secondary outcome of core depression for Group 2 ( P = .02) and Group 3 ( P = .05), but worse physical functioning for Group 3 ( P = .01), compared to Group 1. Conclusions: This study provides evidence of the efficacy of internet‐based psychoeducation interventions for bipolar disorder in reducing depressive symptoms. Further investigation is needed to assess effectiveness in a public program.